THE EFFECT OF INFLATION, INTEREST RATES, AND EXCHANGE RATES ON STOCK PRICES IN BANKING SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019-2024 - Fadilla Putri Siregar; Rico Nur Ilham; Marzuki; Zulfan (PT. Radja Intercontinental Publishing, 2025)
This study is to examine the influence of inflation, interest rates, and exchange rates on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2024 period. The data of this research can be accessed on the official website of www.idx.co.id. The sample in this study is 41 companies. The data analysis tool in this study uses the Data Panel Regression method with the Eviews 12 application tool. The results of the study found that Inflation has a positive but insignificant effect on stock prices, interest rates have a negative and significant effect on stock prices, exchange rates have a positive and significant effect on stock prices.